Institutions in history: Bringing capitalism back in - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2009)
The paper explores possible frontiers of historical-institutionalist analysis. It argues three points: that progress will require a return from a static to a dynamic perspective in which change is no longer a special case but a universal condition of any social order; that theory must not a priori rule out the possibility that institutional change may be more than just random fluctuation, and that it could instead be part of a transition from one state of development to another; and that capturing the dynamic nature of social institutions and of social order in general will require an analytical framework that is adapted to the historical specificities of concrete social formations. Central concepts around which future work in institutionalist political economy may be organized are suggested to be history, development, evolution, and capitalist development. The general idea is that social science stands to benefit, not from ever-advancing abstraction and generalization, but on the contrary from fitting its theoretical template to the historical specificity of the society it is dealing with. – – Der Aufsatz untersucht mögliche Entwicklungslinien historisch-institutionalistischer Forschung in der politischen Ökonomie. Drei Thesen werden vorgestellt: (1) Theoretischer Fortschritt erfordert eine Rückkehr von statischen zu dynamisch-historischen Analysen; (2) Theorien dürfen nicht von vornherein die Möglichkeit ausschließen, dass institutioneller Wandel mehr ist als eine Folge zufälliger Fluktuationen in einem konstanten Merkmalsraum und dass es sich stattdessen um einen Übergang von einem Entwicklungsstadium zum anderen handeln könnte; (3) eine Rückbesinnung auf den dynamischen Charakter sozialer Institutionen, und sozialer Ordnung allgemein, erfordert einen Ansatz, der den historischen Besonderheiten konkreter Gesellschaftsformationen Rechnung trägt. Als zentrale Begriffe künftiger institutionalistischer Forschung in der politischen Ökonomie werden Geschichte, Entwicklung, Evolution und kapitalistische Entwicklung behandelt. Fortschritte in den Sozialwissenschaften werden nicht durch immer weiter vorangetriebene Abstraktion und Verallgemeinerung erreicht, sondern im Gegenteil durch die Spezifizierung ihrer theoretischen Begriffe nach Maßgabe der historischen Besonderheiten der jeweils untersuchten Gesellschaft.
Keywords: 300; Institutionalismus; Institutioneller Wandel; Public Choice; Wirtschaftsgeschichte; Kapitalismus; Evolutionsökonomik